Variability in Development Time and Sex Ratios of Selected Local Populations of Striped Stem Borer Chilo Suppressalis from the Phillipines - G. Demayo, Cesar; T. Angeles, Amelia; T. Romena, Angelita (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Comparison of development times and sex ratios was made for selected local populations of Striped stem horer (SSB) reared un artificial diet. Significant differences in development times were observed among populations. Females had longer larval and total development time compared with the males. No significant differences were observed hetween the sexes in pupal development and weights. Tests of goodness of fit to a 1:1 sex ratio revealed significant excess in males in seven populations of the Striped stem borer (SSB). Significant heterogeneity among the populations in sex ratio was detected. Crosses between populations that differed in sex ratio indicated that sex ratio was a heritable trait. When five populations were allowed to develop on nine rice varieties, it was observed that the total development time did not vary between populations but between rice varieties only. All populations showed significant excess in males across all varieties where the insects were allowed to develop..